The Innovative Approaches to Treating Apnea of Prematurity: From Sensory Stimulation to Aromatherapy - Kocjan, Aleksandra; Papachristoforou, Natalie; Michałka, Daria; Gałuszka, Zuzanna; Makar, Monika; Bartuś, Tomasz; Tekiela, Natalia; Bąk, Emilia; Głowacka, Justyna; Chmiel, Radosław (Quality in Sport, 2025)
Apnea of prematurity (AOP) is a significant health issue affecting neonates born before the 37th week of gestation. It results from the immaturity of respiratory control mechanisms and is often exacerbated by various coexisting factors, which can intensify symptoms and lead to severe health consequences. Despite extensive research on the underlying mechanisms of AOP, a single effective treatment has yet to be identified. Current therapies, such as caffeine administration, are associated with potential adverse effects. Emerging interventions, including sensory stimulation, carbon dioxide inhalation, positional changes, and aromatherapy, offer promising alternatives. These approaches have the potential to complement standard treatments while being less invasive.